A Bibliometric Review: Global Sport Injury Research in Adolescent Athletes - Alzenna Amalia Putri; Kuston Sultoni; Yati Ruhayati; Jajat (Universitas Negeri Semarang, 2025)
Sports injury in adolescent athletes is an important issue that can impact their physical and mental development and future performance. This study analyzed research trends related to injury in adolescent athletes using bibliometric methods based on publications in the Scopus database during the period 2018-2025. The analysis showed that the number of publications has increased significantly since 2018, with a peak in 2024. The United States, the United Kingdom and Australia are the countries with the largest contributions to this research, as well as building extensive international collaborations. Keyword mapping revealed that factors such as age, injury history, body mass index (BMI) and training intensity play a role in increasing injury. Additionally, the study identified research challenges, including language bias and publication selectivity, indicating the need for further exploration with a more diverse range of literature sources. The findings provide insight into sports injury research trends and may guide future studies to increase awareness and injury prevention efforts in adolescent athletes.